Domino intramolecular Diels–Alder reactions to construct a 6/6/5/5 fused tetracyclic framework. Issue 97 (14th October 2015) - Zhao, Gaoyuan; He, Min; Li, Huilin; Duan, Shuangshuang; Yuan, Ziyun; Xie, Xingang; She, Xuegong
Abstract : Heat-promoted domino IMDA reactions to construct a 6/6/5/5 fused tetracyclic framework are developed. Its synthetic application is also demonstrated by an efficient synthesis of 4- epi -hydromitchellene B. Abstract : Domino intramolecular Diels–Alder (IMDA) reactions towards the 6/6/5/5 fused tetracyclic natural products were developed in satisfactory yield and high stereoselectivity. Four rings, six contiguous stereocenters and four C–C bonds were formed in a single operation. 4- epi -Hydromitchellene B was also synthesised efficiently via this strategy.